Differential QoS Support in Web Services Management one service implementation - many levels of service. - Erradi, Abdelkarim (SOA webservices journal.)
Web services are gaining acceptance as the prime technology used to interconnect disparate applications and ease interoperability between heterogeneous and autonomous systems both for internal and external integration. The variation of contexts in which shared Web services could be used and the resulting variation in functional and Quality of Service (QoS) requirements motivate extending Web services management platforms with more sophisticated control mechanisms to cater to differentiated service offerings.